INTERNAL AND EXTERNAL ANALYSIS IN DETERMINING THE OPTIMAL BUSINESS STRATEGY FOR BAEK EXPRESS MIE MSMES - Juliana, Sherlin; Amaturrahman, Roihanah; Wimasada, Caesari Tyas; C.L.S, Clara Regina; Paramartha, Made Bagus (Jurnal Comparative: Ekonomi dan Bisnis, 2025)
This study aims to analyze the business strategy and policy of the Mie Baek Ekspress SME through an internal and external analysis approach. Mie Baek Ekspress is a fast-food business specializing in local-flavored noodles, established in 2022 in Bandung Regency. This research employs a qualitative method with data collection techniques, including in-depth interviews, focus group discussions (FGD), and secondary data analysis. External analysis using PESTEL and Porter's Five Forces reveals that Mie Baek Ekspress faces threats from fluctuating raw material prices and intense competition with similar businesses, such as Mie Gacoan. Internal analysis shows strengths in local taste and strategic location, while weaknesses lie in limited production capacity and underdeveloped digital marketing. The SWOT and TOWS Matrix approach formulates optimal strategies, such as utilizing digital marketing, optimizing operational efficiency, and product development with new menu innovations and eco-friendly packaging. The study concludes that Mie Baek Ekspress should optimize digital marketing, improve operational efficiency, and strengthen product innovation to enhance its competitiveness and business sustainability. The practical implications of this research are expected to help SMEs overcome business challenges and increase competitiveness in the local culinary market.